hsa_circ_0001018 promotes papillary thyroid cancer by facilitating cell survival, invasion, G1/S cell cycle progression, and repressing cell apoptosis via crosstalk with miR-338-3p and SOX4 - Qiang Luo; Feng Guo; Qingfeng Fu; Guoqing Sui (Elsevier, 2021)
We identified a novel interactome, circ_0001018/miR-338-3p/SOX4, in papillary thyroid cancer (PTC), and we intended to confirm the regulatory relationship between the three and to study the effects of the three in PTC. The bioinformatics method was used to screen out the circular RNA and mRNA of interest. A cellular fractionation assay and fluorescence in situ hybridization (FISH) assay were conducted to prove that circ_0001018 and CCT4 (the host gene of circ_0001018) mRNA primarily localized in the cytoplasm of PTC cell lines. By qRT-PCR analysis, the expression of circ_0001018 and SOX4 mRNA was found upregulated while the expression of miR-338-3p was found downregulated in PTC tissues and cells. circ_0001018 silence significantly inhibited the tumor growth in xenografted nude mice. A series of cytological experiments such as a Cell Counting Kit-8 (CCK-8) assay, a 5-ethynyl-2'-deoxyuridine (EdU) assay, cell cycle profiling, wound healing, a transwell assay, and cell apoptosis were conducted and showed that circ_0001018 and SOX4 promoted cell proliferation, migration, and invasion, inhibited cell apoptosis, and reduced the cell cycle arrest at the G1 phase in PTC cells. Compared with circ_0001018 and SOX4, miR-338-3p held the opposite function. The regulatory relationship between circ_0001018 and miR-338-3p, and between miR-338-3p and SOX4 mRNA, was validated using a luciferase reporter gene assay and/or RNA immunoprecipitation (RIP assay). Our findings showed that circ_0001018 acted as the tumor promoter via sponging miR-338-3p to elevate SOX4 expression level in PTC. Importantly, this novel circ_0001018/miR-338-3p/SOX4 axis has the potential to be considered as a therapy target for PTC.